Effect of dietary concentrate to forage ratio on growth performance, rumen fermentation and bacterial diversity of Tibetan sheep under barn feeding on the Qinghai-Tibetan plateau - Liu, Hongjin; Xu, Tianwei; Xu, Shixiao; Ma, Li; Han, Xueping; Wang, Xungang; Zhang, Xiaoling; Hu, Linyong; Zhao, Na; Chen, Yongwei; Pi, Li; Zhao, Xinquan (PeerJ (San Francisco, CA), 2019)
This study aimed to research the effects of different dietary concentrate to forage (C:F) ratio on growth performance, rumen fermentation and bacteria diversity of barn feeding Tibetan sheep. The experiment contains fiver treatments (HS1, HS2 HS3, HS4 and HS5; n = 8, respectively) based on dietary C:F ratios 0:100, 15:85, 30:70, 45:55, and 60:40, respectively. The ruminal bacterial community structure was investigated through high-throughput sequencing of 16S rRNA genes in V4 hypervariable region. The results showed that increasing dietary concentrate feed level from 0% to 60% exerted a positive effect on DMI, BW gain, gain rate and feed conversation ratio (F CR ) in Tibetan sheep. The increases dietary concentrate feed level elevatedNH 3 -N, propionate and valerate concentrations, whereas, reduced molar ratio of acetate to propionate (A/P ratio) ( P < 0.05). For rumen bacterial diversity, increases in dietary concentrate content contributed to lower alpha diversity indexes including Shannon wiener, Chao1 and observed species, meanwhile, significantly increased the abundances of the phylum Bacteroidetes and the genus Prevotella_1 ( P < 0.05). In conclusion, increases dietary concentrate content improved the growth performance and Tibetan sheep fed diets of 45% concentrate obtained a better performance; the inclusion of concentrate in feed changed rumen fermentation from acetate fermentation to propionate fermentation, and improved the energy utilization efficiency of Tibetan sheep; the increased in concentrate content significantly reduced rumen bacteria diversity and changed the abundance of some core bacteria.